The Effect of Skin Factor on Well Production - Dadashzade, M.A.; Mammadova , G.G. (Herald of Azerbaijan Engineering Academy, 2023)
As it is known, during the drilling and operation of oil fields, an additional zone arises where heavy fractions can accumulate. These fractions can be drilling fluid or heavy components such as paraffin, asphaltene, resin, which partially clog the porous medium. All this worsens the permeability of the buttonhole zone. Reducing the permeability of the buttonhole zone partially reduces the productivity of the well. The analysis performed shows that the advance clarification of this zone makes it possible to regulate the proposed method and carry out additional work on the face or buttonhole zone of the post in time.